Fraction and Antibacterial Activity of Bitter Melons (Momordica charantia) in Koi Fish (Cypinus carpio) Infected with Aeromonas salmonicida Bacteria and its Effect on Gills Histopathology - Nadiah Nurandi; Sri Andayani; Yuni Kilawati (Jurnal Penelitian Pendidikan IPA, 2024)
Koi fish (Cyprinus carpio) is a type of freshwater ornamental fish with significant economic value, attracting widespread public interest due to its vibrant colors and agile movements. Therefore, this study introduces a novel approach by evaluating the antibacterial activity of bitter melon extract fraction (Momordica charantia) against A. salmonicida infection in koi fish and its impact on gill histopathology. The novelty of this study lies in the exploration of bitter melon extract fraction as a natural, eco-friendly antibacterial alternative to synthetic antibiotics in aquaculture. This research is crucial as it addresses the growing global concern over antibiotic resistance and the urgent need for sustainable, natural solutions in fish health management. Antibacterial tests were conducted to assess the ability of the bitter melon extract to inhibit bacterial growth, while histopathological analysis aimed to observe the specific changes in gill tissues of infected koi fish. The results revealed that the bitter melon extract fraction significantly reduced bacterial count and improved gill tissue integrity. Histopathological improvements were observed, including reduced hyperplasia, lamellar fusion, edema, and necrosis, indicating tissue recovery. This finding highlights the potential of bitter melon extract fraction as a natural antibacterial agent for controlling bacterial infections in fish, offering an alternative to chemical antibiotics. Further research is needed to determine the optimal dosage and to explore its antibacterial mechanism, ensuring its safe and effective application in aquaculture.